ENHANCING KNOWLEDGE, SKILL, AND ATTITUDE ON ENGLISH VOCABULARY LEARNING THROUGH CREATIVE MEDIA AND GAMIFICATION - Suarliem, Valencia Friska; Suyasa, Ni Luh Christine Prawita Sari; Susanto, Putu Chris; Dewi, Putu Chrisma; Maharani, Ida Ayu Putu Chintya (Seminar Nasional Aplikasi Iptek (SINAPTEK), 2024)
In today's world, being skilled in English is crucial for effective communication. This project, conducted at the Puri Anak Bali Children’s home, focuses on improving English language skills in 11-14-year-old children. Given the challenges in traditional language education, the project aims to enhance vocabulary, pronunciation, and foster a positive attitude toward English learning. Through innovative methods like gamification, creative media, and interactive strategies across four sessions, significant improvements were observed in vocabulary knowledge, pronunciation skill, and learning attitude. The result shows the children indeed underwent significant improvement in vocabulary knowledge, pronunication skill, and learning attitude, thus producing a short Christmas video message for their sponsor. The success of this approach highlights the potential of integrating gamification and creative media for effective language education.